Literature Review : Faktor Risiko Infeksi Necator Americanus (Cacing Tambang) pada Kuku Siswa Sekolah Dasar - Destiana Nurfadillah; Destiani Nurfadillah; Magfhira Zahira Sofa; Rudy Pranata; Popi Sopiah (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Hookworm Necator Americanus Infection Is A Common Public Health Problem Among Elementary School Children, Who Are Often Exposed To Contaminated Soil And Have Poor Hygiene Habits. This Study Aims To Assess The Risk Factors For Necator Americanus Infection Associated With Nail Hygiene In Elementary School Students Through A Literature Review Approach. The Method Used Was Literature Review Of Scientific Articles Obtained Through Google Scholar And Openalex Databases With Relevant Keywords. Of The 106 Articles Selected, 12 Articles Were Obtained That Met The Inclusion Criteria. The Review Showed That Personal Hygiene Behavior, Especially Nail Hygiene, Plays An Important Role In The Transmission Of Necator Americanus Infection. Worm Eggs Can Attach To Dirty Nails And Enter The Child's Body Through Contaminated Hands Or Food. In Addition, The Habit Of Not Washing Hands, Playing On The Ground Barefoot, And A Low Level Of Knowledge Of Clean And Healthy Living Behavior (PHBS) Are Also Supporting Factors For Infection. It Can Be Concluded That Unclean Nails Are A Potential Route For Transmission Of Hookworm Infection In Children. Prevention Efforts Should Involve Personal Hygiene Education, Improved Sanitation Of The School Environment, And Periodic Deworming.